Ethnomathematic Exploration At Agung Jami’ Malang Mosque In Improving Students' Mathematic Problem Solving Ability - Asnawi, Muhammad Hasan; Annisa, Hurriyatul; Ulum, Moh. Miftakhul; Arofah, Nur laili; Hendrawati, Novita Erni (IndoMath: Indonesia Mathematics Education, 2022)
Ethnomathematics has developed and made a major contribution to learning mathematics. One of them is in improving students' mathematical problem solving abilities. The purpose of this study is to explore the ethnomathematics contained in the Agung Jami' Malang Mosque as a means of student learning in improving problem solving skills. The research methods used are ethnography and quantitative. The research instrument is the human instrument, the researcher is directly related to the research, as well as collecting research data through observation, literature, documentation, and tests. In addition, researchers analyzed quantitative data that had been obtained from the results of trials on elementary school students. From the research that has been done, it is found that the ethnomathematics contained in the Agung Jami' Malang Mosque is in the form of geometric shapes, including rectangles, tubes, semi-circles and other geometric shapes. From the results of the trials that have been carried out, it was found that the problem-solving ability of students increased when working on problem-solving problems with the help of ethnomathematics found at the Agung Jami' Malang Mosque.